Using Peer-Editing To Improve Students' Writing Skill (A Classroom Action Research at the Second Year of SMK Negeri 1 Pati in 2010/2011 Academic Year) - Rusmania, Nurina Ika (2012)
The objectives of this study are describing the implementation of peer-editing technique to improve the students' writing ability and describing whether peer-editing technique can improve students' writing skill or not . This study was undertaken in Vocational School of SMK Negeri 1 Pati. The subjects of the research are the second year students of XI Accounting 2 of SMK Negeri 1 Pati, wh o consit of 30 students. The researcher collected the data of the research through observation, interview, document, and test (pre-test, post-test1, post-test2). In this research, the researcher applied Classroom Action Research which requires four steps, namely planning, implementing, observing, and reflecting. In analyzing quantitative data the researcher apllied descriptive comparative technique, while in analyzing qualitative data the writer applied critical analysis technique. The result of this research shows that teaching writing using peer-editing can improve the students' writing ability; it is proved by the improvement of the students' mean score. The mean score of pre-test is 49.6 % , while the mean score of post-test is 79.20%. In ddition, the students also feel interested, enthusiastic, motivated, and easy in writing class.